КУРАШЧИЛАРНИНГ ТЕХНИК ВА ТАКТИК ТАЙЁРГАРЛИГИНИ ТАКОМИЛЛАШТИРИШ - Каримов, Б.Б. (SCIENCE and SOCIETY, 2021)
The article discusses the ways of improving the technical and tactical training of wrestlers in preparation for the competition, reveals the features of the formation of complex technical and tactical movements of wrestlers. The main reason for investigating this question is that the technical and tactical preparation of modern combat has always been on the agenda.